2021
DOI: 10.1021/acs.orglett.1c01676
|View full text |Cite
|
Sign up to set email alerts
|

Complementary Reactivity in Selective Radical Processes: Electrochemistry of Oxadiazolines to Quinazolinones

Abstract: Electrochemistry has recently emerged as a sustainable approach for efficiently generating radical intermediates utilizing eco-friendly electric energy. An electrochemical process was developed to transform 1,2,4-oxadiazolines under mild conditions. The electrochemical N−O bond cleavage at a controlled oxidation potential led to the selective synthesis of quinazolinone derivatives that could not be obtained by photocatalytic radical processes, indicating complementary reactivities in radical processes. The ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
2
2
0
Order By: Relevance
“…Besides the above-mentioned spiro-azalactam, benzimidazole, and sulfoximine products, quinazolinones were generated selectively from 1,2,4-oxadiazolines by electrochemistry through heterolytic N–O bond cleavage at a controlled oxidation potential, indicating complementary reactivities in radical processes (Scheme ). Notably, an identical reaction profile to give quinazolinones in the presence of oxygen under thermal conditions was reported by the Chiba group …”
Section: N–o Bond Activation In 124-oxadiazolinessupporting
confidence: 63%
See 1 more Smart Citation
“…Besides the above-mentioned spiro-azalactam, benzimidazole, and sulfoximine products, quinazolinones were generated selectively from 1,2,4-oxadiazolines by electrochemistry through heterolytic N–O bond cleavage at a controlled oxidation potential, indicating complementary reactivities in radical processes (Scheme ). Notably, an identical reaction profile to give quinazolinones in the presence of oxygen under thermal conditions was reported by the Chiba group …”
Section: N–o Bond Activation In 124-oxadiazolinessupporting
confidence: 63%
“…Based on the redox potentials of reactivities in radical processes (Scheme 3). 66 Notably, an identical reaction profile to give quinazolinones in the presence of oxygen under thermal conditions was reported by the Chiba group. 67…”
Section: N−o Bond Activation In 124-oxadiazolinessupporting
confidence: 52%
“…[23] It should be mentioned that Cho recently showed that iminyl radicals can induce similar transformations albeit with unsatisfactory regioselectivity. [24] To interrogate two regulatory pathways in the formation of skeletally rearranged lactam isomers, we conducted density functional theory (DFT) calculations (Figure 1 b-d). Reductive SET of 3 a leads to a smooth NÀO bond cleavage with 13.0 kcal mol À1 barrier (see the Supporting Information for details).…”
mentioning
confidence: 99%
“…The lactam formation was also found to be efficient even with substrates containing additional groups at the b-position relative to the carbonyl group. For instance, d-lactams having one or two b-phenyls were readily obtained (23,24). Additionally, 10 % of NÀPh amide (24') was also formed, which can be generated by the Smiles-type rearrangement.…”
mentioning
confidence: 99%